Implementation of Austro-Hungarian legislation on universal suffrage in Eastern Galicia at the XX century - Baran, Angelika (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
In the given article the author describe the election campaigns to the Austrian Parliament at the XX century, the author also depicts the process of formation of the Ukrainian political elite and its parliamentary struggle against the defending national rights and freedoms of Ukrainian population of Eastern Galicia.